Direct medical costs associated with different lines of therapy for colorectal cancer patients. (April 2013) - Ray, Saurabh; Bonthapally, Vijayveer; Meyer, Nicole M; Miller, Jeffrey D; Bonafede, Machaon M; Curkendall, Suellen M
SUMMARY  Aim: To evaluate the disease-specific expenditures incurred by colorectal cancer (CRC) patients with one, two, and three or more lines of therapy.Methods: The Truven Health MarketScan® Research Databases were used to identify adults with incident CRC from 2005 to 2009. Healthcare expenditures were measured from initiation through to follow-up and individual therapy line.Results: Among 13, 670 CRC patients, 67.5% had one line of therapy, 20.7% had two and 11.8% had three or more. Monthly expenditures averaged US$12, 523. Monthly first-line therapy costs averaged US$12, 067, increasing to US$13, 315 during second-line therapy and to US$14, 648 during third-line therapy. Patient out-of-pocket expenses were a small (1.9%) contributor to total costs.Conclusion: CRC presents a significant economic burden to payers with important cost differences according to how patients are treated.